A numerical-experimental investigation on the aerodynamic performance of CAARC building models with geometric modifications. Issue 180 (September 2018) - Alminhana, G.W.; Braun, A.L.; Loredo-Souza, A.M.
Abstract: This paper presents the results of a numerical-experimental investigation carried out with the purpose to evaluate the aerodynamic performance of CAARC tall building models with different cross-section configurations. A numerical model based on the Taylor-Galerkin two-step scheme and the Finite Element Method is adopted. Turbulence is described using LES and a synthetic inflow turbulence generator. Experimental tests were performed at the Prof. Joaquim Blessmann Boundary Layer Wind Tunnel considering CAARC tall building models with cross-section modifications based on chamfered and recessed corners. Some of the wind tunnel predictions obtained here are compared with results obtained from the numerical model proposed in this work, where two and three-dimensional meshes are utilized. Comparisons are also performed considering results obtained from other authors in similar studies. From the present investigation, it was observed that the wind action on tall buildings is significantly influenced by the geometric configuration of the building corners, which may lead to important reductions in the aerodynamic forces. Through a direct comparison of results between numerical and experimental simulation, we can see that both reach a convergence of results, thus indicating the potential of use of CFD in the modern aerodynamic investigation of buildings. Highlights: Small geometric modifications can reduce significantly the aerodynamic coefficients. The size of the corner modification modifies the aerodynamic coefficients. 3D models with chamfered and recessed corners leads to a similar performance in drag. Modified corners change the pressure distribution in the facades and velocity nearby.